An engineered retroviral proteinase from myeloblastosis associated virus acquires pH dependence and substrate specificity of the HIV-1 proteinase - Konvalinka, J; Horejsí, M; Andreánsky, M; Novek, P; Pichová, I; Bláha, I; Fábry, M; Sedlácek, J; Foundling, S; Strop, P (The EMBO journal, 1992)
In an attempt to understand the structural reasons for differences in specificity and activity of proteinases from two retroviruses encoded by human immunodeficiency virus (HIV) and myeloblastosis associated virus (MAV), we mutated five key residues predicted to form part of the enzyme subsites S1, S2 and S3 in the substrate binding cleft of the wild-type MAV proteinase wMAV PR. These were changed to the residues occupying a similar or identical position in the HIV-1 enzyme. The resultant mutated MAV proteinase (mMAV PR) exhibits increased enzymatic activity, altered substrate specificity, a substantially changed pH activity profile and a higher pH stability close to that observed in the HIV-1 PR. This dramatic alteration of MAV PR activity achieved by site-directed mutagenesis suggests that we have identified the amino acid residues contributing substantially to the differences between MAV and HIV-1 proteinases.
Keywords: Substrate Specificity; Protein Engineering; HIV-proteasa; Molecular Sequence Data; molekulární sekvence - údaje; sekvence aminokyselin; Protein Conformation; endopeptidasy; Endopeptidases; HIV Protease; mutageneze cílená; Amino Acid Sequence; Kinetics; proteinové inženýrství; substrátová specifita; Retroviridae; Hydrogen-Ion Concentration; Mutagenesis, Site-Directed; koncentrace vodíkových iontů; kinetika; konformace proteinů